2011
DOI: 10.1007/s11046-011-9404-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Activity of Medicinal Plant Extracts Against Oral Candida albicans and Proteinases

Abstract: Proteinases produced by Candida albicans are one kind of virulence factor expressed that contribute to adherence and invasion of host tissue. Proteinase inhibitor of human immunodeficiency virus in experimental candidiasis suggested reduction in fungal infection, and medicinal plants could be a source of alternative agent to prevent diseases. In this study, we investigated the production of proteinases by C. albicans from clinical isolates and the action of plant extracts against strains of C. albicans and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
8
0
3
Order By: Relevance
“…This result corroborates with Pereira et al, 35 who demonstrated the antifungal activity of n-butanol leaf extracts of S. obtusifolium in deleterious effects on the morphology and viability of biofilms treated with this extract, suggesting investigation as a potential alternative for the treatment of Candida biofilms. Höfling et al 36 confirmed the important activity of fractionated plant extracts on clinical isolates of C. albicans and inhibition of fungal membrane proteolytic activity, demonstrating an important alternative to control and prevent candidiasis. As for the fractionated bark extracts of S. obtusifolium (LC) in this study, the fractioning of the LC extract did not potentiate its action against C. albicans.…”
Section: Jcdpmentioning
confidence: 95%
“…This result corroborates with Pereira et al, 35 who demonstrated the antifungal activity of n-butanol leaf extracts of S. obtusifolium in deleterious effects on the morphology and viability of biofilms treated with this extract, suggesting investigation as a potential alternative for the treatment of Candida biofilms. Höfling et al 36 confirmed the important activity of fractionated plant extracts on clinical isolates of C. albicans and inhibition of fungal membrane proteolytic activity, demonstrating an important alternative to control and prevent candidiasis. As for the fractionated bark extracts of S. obtusifolium (LC) in this study, the fractioning of the LC extract did not potentiate its action against C. albicans.…”
Section: Jcdpmentioning
confidence: 95%
“…Some other reports have also described the anti-virulence activity from certain essential oils or its constituents such as inhibition of germ tubes and proteinase production in Candida spp. (Pozatti et al, 2010;Hofling et al, 2011). Since adherence and dimorphic transition are principle steps in initiation of biofilm development we hypothesize that these essential oils or its compounds possessing anti-virulence properties might be fairly active against biofilm development.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products such as medicinal plants could comprise an option for the treatment of infectious diseases, in that there is supporting information on the use of the plant in Traditional Medicine and when there are results of experimental studies reporting antimicrobial activity (Andrews and Harris, ). The empirical use of plants for treating diseases produced by Candida in different parts of the world possesses a long history (Höfling et al, ); at present, the increased use of this type of Medicine could be a consequence of the resistance of pathogen agents to pharmaceutical antibiotics (van Minnebruggen et al, ). Different pharmacological in vitro evaluations and clinical trials have confirmed the antifungal properties of extracts obtained from the plant species A. pichinchensis (Castañeda et al, ; Romero et al, ; Kok et al, ).…”
Section: Discussionmentioning
confidence: 99%